Effective utilisation of poultry byproduct meal as an ingredient in the diet of Genetically Improved Farmed Tilapia (GIFT), cultured in reservoir cages in Tamil Nadu, Ssouth India - Felix, N.; Prabu, E.; Upadhyay, Aurobinda (Indian Journal of Fisheries, 2020)
Evaluation of efficiency of poultry byproduct meal (PBM) as alternative protein source by replacing fish meal (FM) in the diets of GIFT strain of tilapia (Oreochromis niloticus) was carried out in cages installed in Poondi Reservoir, Tamil Nadu, South India. Six isonitrogenous (30% protein) and isolipidic (7% lipid) diets were formulated using graded levels of PBM protein  to replace FM protein. Each diet was fed to two replicate groups of GIFT tilapia with  mean initial weight of 20.38±0.0678 g, for 60 days in cages. The best growth performances in terms of mean weight gain (116.72 g), best food conversion ratio (FCR, 1.14) and maximum hepatosomatic index (HIS, 2.47) values were observed in GIFT tilapia fed  PBM diet  with 40% fish meal replacement. However, no significant (p>0.05) differences were observed in the whole body proximate composition of fish fed control and treatment diets. It was concluded that, poultry byproduct meal can replace 40% fish meal protein in the diets of GIFT tilapia cultured in reservoir cages without compromising growth, FCR and whole body proximate composition. The study suggests that poultry byproduct meal could effectively replace fish meal without affecting growth and feed conversion of the fish. The findings thus may pave a productive way for reducing environmental pressure of disposal of slaughter house waste.Keywords: Feed ingredient, Fish meal, GIFT tilapia, Poultry byproduct meal, Reservoir cages, Waste utilisation